FRI0217 Impact of rituximab in combination with leflunomide and rituximab retreatment with two different dosages on patient-reported outcomes: results from a multicenter randomized placebo controlled investigator initiated clinical trial in active rheumatoid arthritis (AMARA-STUDY). (15th June 2017) - Köhm, M; Rossmanith, T; Dauth, S; Alten, R; Aringer, M; Backhaus, M; Burmester, G; Feist, E; Kellner, H; Krüger, K; Müller-Ladner, U; Rubbert-Roth, A; et al.
Abstract : Background: Use of biologicals such as Rituximab (RTX) in Rheumatoid Arthritis (RA) is effective and often only licensed in combination with Methotrexate (MTX). In cases of contraindications to or intolerances of MTX other cDMARDs are frequently used without robust data from RCTs. In addition, different strategies of retreatment of RTX are available. Objectives: To demonstrate efficacy on patient-reported outcomes (PROs) of RTX in combination with leflunomide (LEF) in a multicenter investigator-initiated placebo (PLA)-controlled RCT in Germany. Methods: A total of 189 patients with active RA (DAS28>3.2 and at least 3 SJC and 3 TJC) despite stable LEF treatment were screened for a 52-weeks double-blind placebo controlled RCT. Patients were randomized to receive either two-times 1000mg RTX i.v. followed by a retreatment at week 24 with two-times 1000 (RTX-RTXhigh) or 500mg (RTX-RTXlow) or two times PLA at baseline, followed by a retreatment of RTX of either two-times 1000 (PLA-RTXhigh) or 500mg (PLA-RTXlow) at week 24. Adult patients who had inadequate response to more than one antiTNF or failed more than three cDMARDs were excluded. PROs (HAQ, FACIT-F, SF36) were measured at each visit until week 52. Treatment effects on PROs were determined by differences from baseline to week 16, 24 and week52. Results: Of 189 screened patients 148 were randomized (mean age 56 years; mean proportion of RF-and antiCCP-positivity 58.4% and 55.7% in the RTX-group; 74% female). DAS28 at baseline was 5.55 for RTX and 5.53 in the PLA-group. All baseline-characteristics were well balanced between treatment groups. An improvement in HAQ from baseline to week 16 was seen with a mean delta of -0.23 in the RTX-group (MCID) vs. -0.11 for PLA. In the RTX-group, retreatment until week 52 resulted in stable HAQ-values compared to week24 independent from its dosage. FACIT-F values increased in the RTX-group from baseline to weeks 16, 24 and 52 by 11.87, 12.3 and 14.25, respectively. All physical and mental domains of the SF36 showed a pronounced increase of levels at week 16 compared to baseline in the RTX-group (Figure 1 ). A total of 372 adverse events (AE) were observed during the one-year studyperiod, only 14 classified as severe (10 in RTX and 4 in PLA). 43 serious adverse events were reported, 28 of them in the RTX-group during the placebo-controlled period. Conclusions: Efficacy of LEF plus RTX was demonstrated not only by measurements of disease activity (as presented previously) but also by measurements of PROs (HAQ, FACIT-F, SF36). This treatment regime showed equal effect sizes compared to the combinational therapy of MTX plus RTX. The treatment with LEF plus RTX illustrated an acceptable safety profile. Disclosure of Interest: M. Köhm Grant/research support from: Pfizer, Janssen, Consultant for: Janssen, T. Rossmanith Grant/research support from: Janssen, Pfizer, Roche, S. Dauth: None declared, R. Alten Grant/research support from: Roche, M. Aringer Grant/research support from: Roche, M. Backhaus Grant/research support from: Roche, G. Burmester Grant/research support from: Roche, E. Feist Grant/research support from: Roche, H. Kellner Grant/research support from: Roche, K. Krüger Grant/research support from: Roche, U. Müller-Ladner Grant/research support from: Roche, A. Rubbert-Roth Grant/research support from: Roche, H.-P. Tony Grant/research support from: Roche, S. Wassenberg Grant/research support from: Roche, H. Burkhardt Grant/research support from: Roche, Pfizer, Speakers bureau: Pfizer, BMS, F. Behrens Grant/research support from: Roche, Pfizer, Janssen, Speakers bureau: BMS, Janssen, Pfizer, AbbVie